Secondary Students' Understanding of Genetics Using BioLogica: Two Case Studies - Tsui, Chi-Yan; Treagust, David (Springer, 2013)
This chapter reexamines our research on secondary students’ understanding of genetics in terms of gene conceptions and reasoning when they learned genetics with multiple external representations (MERs). In our Australian study, teachers in three Perth schools included interactive BioLogica activities which feature manipulable MERs to varying degrees in their teaching. In our Hong Kong study, students used BioLogica in an after-school program for which the teacher and researcher provided bilingual support and both group and individual feedback. The results of our studies—from a cross-case analysis of students’ gene conceptions and genetics reasoning based on interviews, online two-tier tests, computer log files, and other data sources—indicated that most students improved their understanding of genetics to varying extent in terms of sophistication of their gene conceptions and the six types of genetics reasoning. The findings suggest that MERs supported understanding of genetics but not for all students. We compare the Australian and Hong Kong studies in terms of students’ genetics reasoning, explore how students learned complex content in biology using MERs within different learning contexts, and discuss the potential of visual-graphical and bilingual representations for scaffolding the learning of English language learner (ELL) students.